151k views
3 votes
If you apply the changes below to the cube root parent function, F(x) = x,what is the equation of the new function?• Translate 1 unit right.• Translate 1 unit up.A. G(x) = *fx-1-1B. G(x) = {x-1+1aC. G(x) = x+1+1D. G(x) = {x+1-1O

If you apply the changes below to the cube root parent function, F(x) = x,what is-example-1
User Qedi
by
4.5k points

1 Answer

5 votes

Recall that a function h(x) translated n units to the right, is represented by


l(x)=h(x-n),

and h(x) translated n units up is represented by


l(x)=h(x)+n\text{.}

Therefore, the given function translated 1 unit to the right and 1 unit up is:


G(x)=\sqrt[3]{x-1}+1.

Answer:


G(x)=\sqrt[3]{x-1}+1.

User Lopper
by
4.4k points